Effectiveness of facemasks for opening a university campus in Mississippi, United States – a modelling study. Issue 8 (17th November 2022) - MacIntyre, C. Raina; Costantino, Valentina; Bian, Linkan; Bethel, Cindy
Abstract: Background: Universities are at risk for COVID-19 and Fall semester begins in August 2020 for most campuses in the United States. The Southern States, including Mississippi, are experiencing a high incidence of COVID-19. Aims: The objective of this study is to model the impact of face masks and hybrid learning on the COVID-19 epidemic on Mississippi State University (MSU) campus. Methods: We used an age structured deterministic mathematical model of COVID-19 transmission within the MSU campus population, accounting for asymptomatic transmission. We modeled facemasks for the campus population at varying proportions of mask use and effectiveness, and Hyflex model of partial online learning with reduction of people on campus. Results: Facemasks can substantially reduce cases and deaths, even with modest effectiveness. Even 20% uptake of masks will halve the epidemic size. Facemasks combined with Hyflex reduces epidemic size even more. Conclusions: Universal use of face masks and reducing the number of people on campus may allow safer universities reopening.